2014
DOI: 10.2310/7750.2013.13026
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Fasciitis Occurring under Treatment with Natalizumab for Multiple Sclerosis

Abstract: Background: Eosinophilic fasciitis is a rare sclerosing syndrome with a poorly understood etiology. Objective: We report a case of eosinophilic fasciitis in a 40-year-old man undergoing treatment with natalizumab for multiple sclerosis. Natalizumab is a selective adhesion molecule inhibitor that prevents interaction of leukocytes with endothelial cells. Peripheral blood eosinophilia has been described under treatment with natalizumab, but we herein report the first case to our knowledge of eosinophilic fasciit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…PubMed database was searched twice by (CF, RH, LD) using the search terms "eosinophilic/eosinophilia natalizumab" and "eosinophilic/eosinophilia Tysabri" (date of last PubMed search 29.10.2020). Hereby 9 articles (Abbas et al, 2011;Florek et al, 2010;Curto et al, 2016;Yasuda et al, 2019;Bujold et al, 2014;André et al, 2010;Rocher et al, 2010;Mihalova et al, 2015;Beales, 2019) dealing with blood eosinophilia with and without clinical symptoms during natalizumab treatment were identified. We compared the data of those studies to our own data and analyzed all reported cases of asymptomatic and symptomatic eosinophilia in NTZ treated patients.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…PubMed database was searched twice by (CF, RH, LD) using the search terms "eosinophilic/eosinophilia natalizumab" and "eosinophilic/eosinophilia Tysabri" (date of last PubMed search 29.10.2020). Hereby 9 articles (Abbas et al, 2011;Florek et al, 2010;Curto et al, 2016;Yasuda et al, 2019;Bujold et al, 2014;André et al, 2010;Rocher et al, 2010;Mihalova et al, 2015;Beales, 2019) dealing with blood eosinophilia with and without clinical symptoms during natalizumab treatment were identified. We compared the data of those studies to our own data and analyzed all reported cases of asymptomatic and symptomatic eosinophilia in NTZ treated patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reviewing the scientific literature leads to identification of 4 additional case reports of natalizumab treated RRMS patients with symptomatic eosinophilia (Curto et al, 2016;Yasuda et al, 2019;Bujold et al, 2014;André et al, 2010) and 3 cases with asymptomatic marked eosinophilia with cell counts >1 G/l (Abbas et al, 2011). In our single center cohort we found 1 case of symptomatic eosinophilia, 6 cases of asymptomatic marked eosinophilia and 37 cases of mild eosinophilia (which all remained asymptomatic) of in total 115 NTZ treated RRMS patients with at least one eosinophil count since July 2016.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the latter report Shulman disease did not relapse after subsequent infusion of natalizumab. 4 In our case the onset of fasciitis after the drug administration and the rapid recurrence after a Did the reaction reappear when a placebo was given? −1 +1 0 0…”
Section: Eosinophilic Fasciitis Induced By Natalizumab In a Patient Amentioning
confidence: 65%
“…The development of PML in one patient in SENTINEL and a second patient in the corresponding extension study prompted discontinuation of the trial approximately 1 month early [Rudick et al 2006]. No increased risk of lymphoma, malignant melanoma or hypereosinophilia was reported in these studies [Abbas et al 2011; Bujold et al 2014; Mullen et al 2008]. No increase in infection among patients receiving natalizumab, compared with placebo, was found [Polman et al 2006; Rudick et al 2006], but postmarketing studies identified a slight excess of herpes virus infections [Fine et al 2013; Holmen et al 2011] with rare cases of fatal herpes encephalitis [Biogen Idec, 2013; Kwiatkowski et al 2012] and meningitis [Biogen Idec, 2013; Shenoy et al 2011; Valenzuela et al 2014].…”
Section: Natalizumabmentioning
confidence: 99%